(untitled) (Global Journal of Science Frontier Research, 2017)
In the article it is proposed to expand the framework of the standard model of generation and distribution of cosmic rays and, in addition to the model of inelastic interactions of the protons of the radiation belt and cosmic radiation with the nuclei of atoms of the residual atmosphere, to consider the resonant mechanism of generation of secondary electrons and positrons in the near-Earth space environment. Based on the analysis of the data obtained in the PAMELA experiments, FERMI and AMS, a plot of the resonance curves for the generation of secondary particles was constructed and the probable cause is named of the relative growth of the positron flux in the total flux of secondary electrons and positrons, starting with the proton energy above W = 5 GeV.